Allitérations, assonances et figuralismes : de leur histoire à leur utilisation en phonétique du FLE - Claire Pillot-Loiseau; Claudia Schweitzer (Corela)
This article first presents a historical section showing the importance of alliterations and assonances in French literature, but also that of musical figuralism. Alliterations and assonances are characterized by the repetition of consonants or vowels, encouraging to any pedagogical pronunciation activity: they improve memorization, comprehension, and pronunciation. After this first section, a selection of several literary texts, some of which are set to music, is proposed, for their pedagogical use in improving the pronunciation of French as a foreign language: opening towards a fine perception of foreign sounds and pronunciation games, the work of diction and the access to a pleasure of speaking, help concerning some specific pronunciation errors (continuity of fricatives without affricates production, distinction between unvoiced and voiced plosives, sonorous consonants /lmnr/ and distinction between /r/ and /l/), "articulatory figuralism".